Analysis Of Employee Engagement And Job Satisfaction As An Effort To Increase Work Effectiveness On CU. Cinta Kasih Tigapanah - Nishaclara Br Ginting; Feronica Simanjorang (SEAN Institute, 2023)
This study seeks to analyze employee engagement and job satisfaction as an effort to increase work effectiveness in CU. Cinta Kasih Tigapanah. The form of research used in this study is qualitative research. Data collection is carried out through documentation, interview, and observation techniques. The data analysis process is carried out by means of data collection, data reduction, data presentation, then drawing conclusions. The results of the research conducted show that the application of employee engagement and job satisfaction as an effort to increase employee work effectiveness has gone well and it can be seen that employees in terms of materials, skills, directions, and meeting employee job satisfaction so as to produce employee work effectiveness while carrying out their duties. This is shown by the opinions of employees towards the company both in terms of the dimension of employee engagement and the dimension of job satisfaction in increasing work effectiveness efforts.